(untitled) (San Diego, Calif., 1988)
This volume covers cellulose and hemicellulose and includes proven and reproducible methods for research related to the conversion of carbohydrate polymers to usable monomeric units. Sections on the preparation of biomass materials and of substrates are included, as are sections on analytical methods and on the purification and assay of enzymes.
Keywords: Biopolymers,Polyme sinh học